1992
DOI: 10.1111/j.1532-5415.1992.tb02018.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Tolerance in Women: The Effects of Age, Body Composition, and Sex Hormones

Abstract: Age per se, and to a lesser extent BMI and WHR, but not levels of endogenous sex steroids, contribute to the physiological decline in glucose tolerance in older women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…[76][77][78][79][80][81] HRT improves carbohydrate metabolism, as evidenced by a decrease in hyperglycemia and hyperinsulinemia, and body fat distribution. [81][82][83][84][85] HRT also appears to im-prove vascular reactivity, 86,87 translating to an increase in nitric oxide availability, which is a potent inhibitor of PAI-1 expression. 88,89 While the intrinsic fibrinolytic system appears to be intimately related to the aforementioned estrogen-related metabolic and physiologic factors, the precise estrogen-fibrinolytic interaction is unknown and may be multifactorial.…”
Section: Hormone Replacement Therapymentioning
confidence: 99%
“…[76][77][78][79][80][81] HRT improves carbohydrate metabolism, as evidenced by a decrease in hyperglycemia and hyperinsulinemia, and body fat distribution. [81][82][83][84][85] HRT also appears to im-prove vascular reactivity, 86,87 translating to an increase in nitric oxide availability, which is a potent inhibitor of PAI-1 expression. 88,89 While the intrinsic fibrinolytic system appears to be intimately related to the aforementioned estrogen-related metabolic and physiologic factors, the precise estrogen-fibrinolytic interaction is unknown and may be multifactorial.…”
Section: Hormone Replacement Therapymentioning
confidence: 99%
“…A slight increase of fasting glucose levels with increasing age was described in previously published studies [13,14], but these finding did not support a strong correlation. The Baltimore Longitudinal Study of Aging could demonstrate a progressive decline in glucose tolerance in women from early to late adulthood [25]. In the longitudinal Medical Research Council Cognitive Function and Ageing Study, which included over 18,000 individuals aged 65 years and older, mortality from all causes, cardiovascular and ischemic heart disease increased with increasing glycated hemoglobin (HbA1c) values [26].…”
Section: Discussionmentioning
confidence: 99%
“…Five of nine observational studies showed no significant differences in glucose levels during OGTT between different cycle phases [36,[38][39][40]42], whereas four studies showed significant differences [34,36,37,41]. In three of these four studies, glucose levels were significantly lower in the FP than in the LP [34,37,41]; Walsh and O'Sullivan reported the opposite result [36].…”
Section: Impact Of the Menstrual Cycle On Glucose Tolerancementioning
confidence: 90%
“…To date, studies examining the influence of menstrual cycle phases on glucose metabolism via OGTTs [34][35][36][37][38][39][40][41][42] in humans are scarce and have provided contradictory results.…”
Section: Impact Of the Menstrual Cycle On Glucose Tolerancementioning
confidence: 99%